Cardioprotective Effects of Bosentan in Rats Subjected to Lung Ischemia–Reperfusion Injury - Şevki Mustafa Demiröz; Ayşegül Küçük; Esra Tekin; Sibel Söylemez; Hanife Yılmaz; Şaban Cem Sezen; Muharrem Atlı; Hüseyin Demirtaş; Abdullah Özer; Yusuf Ünal; Mustafa Arslan (Medicina)
Objective: This study aimed to investigate the cardioprotective effects of bosentan, an endothelin receptor antagonist, in a rat model of lung ischemia–reperfusion (I/R) injury, with a focus on myocardial tissue involvement. Methods: Twenty-four male Wistar rats were randomly assigned to four groups: sham, bosentan, I/R, and I/R + bosentan. Lung I/R injury was induced by hilar clamping for 45 min, followed by 60 min of reperfusion. Bosentan (30 mg/kg) was administered intraperitoneally 30 min prior to the procedure. Myocardial tissue was evaluated histopathologically for structural disorganization, inflammation, fibrosis, and edema. TGF-β1 protein levels in myocardial tissue were compared across the groups using β-actin as the loading control. ELISA was used to quantify ET-1, NF-κB, and p53 levels, while spectrophotometric analysis was employed to assess MDA levels and the activities of SOD and CAT enzymes in heart tissue. Results: The I/R group exhibited significant myocardial disorganization, inflammation, and interstitial edema compared to the sham and bosentan groups. Bosentan treatment markedly ameliorated these histopathological alterations. Additionally, the I/R group showed elevated levels of ET-1, NF-κB, p53, and MDA, along with reduced SOD and CAT activities; these changes were significantly attenuated by bosentan administration. Bosentan treatment significantly reduced myocardial ET-1 levels (from 136.88 ± 5.02 to 120.18 ± 2.67 nmol/g, p = 0.003), NF-κB levels (from 0.87 ± 0.04 to 0.51 ± 0.03 ng/mg, p = 0.002), and TGF-β1 expression (from 1.72 ± 0.10 to 0.91 ± 0.08 relative units, p = 0.001). Moreover, bosentan increased antioxidant enzyme activities, elevating SOD levels from 21.45 ± 1.23 to 32.67 ± 1.45 U/mg protein (p = 0.001) and CAT levels from 15.22 ± 0.98 to 25.36 ± 1.12 U/mg protein (p = 0.002). Conclusions: Bosentan exerts cardioprotective effects in rats subjected to lung I/R injury by reducing myocardial damage, inflammation, and oxidative stress. These findings suggest that bosentan may serve as a potential therapeutic agent for preventing remote organ injury associated with pulmonary I/R.